Rapid coeval black hole and host galaxy growth in MRC1138-262: The hungry spider - Seymour, Nick; Altieri, B.; De Breuck, C.; Barthel, P.; Coia, D.; Conversi, L.; Dannerbauer, H.; Dey, A.; Dickinson, M.; Drouart, G.; Galametz, A.; Greve, T.; et al. (2012)
We present a detailed study of the infrared spectral energy distribution of the high-redshift radio galaxy MRC1138-26 at z = 2.156, also known as the Spiderweb Galaxy. By combining photometry from Spitzer, Herschel, and LABOCA we fit the rest-frame 5-300 µm emission using a two-component, starburst, and active galactic nucleus (AGN) model. The total infrared (8-1000 µm) luminosity of this galaxy is (1.97 ± 0.28) ×1013 L ? with (1.17 ± 0.27) and (0.79 ± 0.09) ×1013 L ? due to the AGN and starburst components, respectively. The high derived AGN accretion rate of 20% Eddington and the measured star formation rate (SFR) of 1390 ± 150 M ?yr-1 suggest that this massive system is in a special phase of rapid central black hole and host galaxy growth, likely caused by a gas-rich merger in a dense environment. The accretion rate is sufficient to power both the jets and the previously observed large outflow. The high SFR and strong outflow suggest that this galaxy could potentially exhaust its fuel for stellar growth in a few tens of Myr, although the likely merger of the radio galaxy with nearby satellites suggests that bursts of star formation may recur again on timescales of several hundreds of Myr. The age of the radio lobes implies the jet started after the current burst of star formation, and therefore we are possibly witnessing the transition from a merger-induced starburst phase to a radio-loud AGN phase. We also note tentative evidence for [C II]158 µm emission. This paper marks the first results from the Herschel Galaxy Evolution Project (Project HeRGÉ), a systematic study of the evolutionary state of 71 high-redshift, 1 < z < 5.2, radio galaxies. © 2012. The American Astronomical Society. All rights reserved.